Synthesis and antibacterial potential of Loranthus pulverulentus conjugated silver nanoparticles. Issue 11 (21st July 2022) - Subhani, Muhammad Ali; Irshad, Muhammad; Nazir, Asma; Hafeez, Muhammad; Ali, Shaukat
Abstract: The green method is not only harmonious to our environment but saves time and is comparatively cheaper than other methods. The current study is aimed to synthesize the silver nanoparticles (AgNPs) using the green method by using the leaves of Loranthus pulverulentus Wall (LPW) which functioned as a reducing as well as capping agent. The synthesis of biogenic AgNPs was confirmed by UV–Vis spectroscopy (UV–Vis.), Scanning electron microscopy (SEM), X‐ray diffraction (XRD), energy dispersive X‐ray (EDX), and Fourier transform infrared (FTIR). The absorbance maxima of the synthesized AgNPs were observed in the range of 405–435 nm. The SEM was used to find out the size and shape of the synthesized AgNPs, which revealed that the NPs were rectangular having sizes from 05 to 16 nm. XRD revealed that the synthesized NPs were crystalline and face‐centered cubic (FCC). EDX analysis reflected the elemental composition of the synthesized product and showed that the percentage of silver = 92. FTIR was used to confirm the functional groups responsible for the reduction and stabilization of silver ions. It revealed that biomolecules present in plant extract were responsible for the reduction and stabilization of silver ions. The effect of temperature, pH, reaction time, silver nitrate concentration, and plant extract concentration on the synthesis of AgNPs were also investigated. The synthesized silver nanoparticles were tested against four bacterial strains which showed strong antibacterial activity. We conclude that biogenic silver nanoparticles could be used as antibacterial agents to treat various diseases. Research Highlights: Loranthus pulverulentus Wall leaf extract mediated synthesis of silver nanoparticles. Effects of pH 3, 4, 6, 9, and 11, reaction time 5, 10, 20, 40 min, 1, 2, and 3 h, temperature 30, 40, 50, 60°C, silver nitrate concentration 0.5, 1.0, 2.0, and 3.0 mM and plant extract concentration 0.5, 1.0, 2.0, and 3.0 g on the AgNPs synthesis were also studied Scanning electron microscopy analysis revealed a small size of synthesized silver nanoparticles (8 nm). The synthesized silver nanoparticles were found effective against various bacterial pathogens. Abstract : Graphical representtation of resesrch work summary.